Contingency Leadership Style and Organizational Performance in the Nigerian Public Service - Joel Bisina; Goodluck Omamuyovwi Afonughe (Universitas Medan Area, 2026)
This study examines the influence of contingency leadership on organizational performance in Nigeria’s public service amid persistent administrative and economic challenges. It aims to analyze how leadership adaptability affects efficiency, accountability, and service delivery. The study employs a qualitative approach, drawing on relevant theoretical and empirical literature to explore contingency leadership as the main analytical framework. Grounded in contingency theory, the research emphasizes that leadership effectiveness depends on the alignment between leadership style and situational factors such as task structure, employee competence, and organizational environment. The findings indicate that adaptive leadership—characterized by flexibility in decision-making, communication, and supervision—significantly enhances organizational performance. Conversely, rigid leadership styles tend to reduce employee motivation and hinder innovation. The study concludes that the adoption of contingency-based leadership, supported by continuous capacity development and institutional reform, is essential for improving governance and public service performance in Nigeria. It recommends implementing context-sensitive leadership strategies, strengthening leadership training, improving communication systems, and using data-driven decision-making to achieve sustainable organizational outcomes.